Use Of Audio Media And Films In Teaching English - Utashev Kuldash Xapizovich (Academia One, 2024)
The utilization of audio media and films in the instruction of the English language to students has proven to be highly effective. By incorporating these multimedia resources into the classroom, educators can enhance the learning experience and promote language acquisition dynamically and engagingly. Audio media, such as podcasts and recorded dialogues, allow students to improve their listening and comprehension skills. Additionally, films offer visual context and cultural insights, allowing learners to develop their vocabulary, grammar, and pronunciation in a more authentic and contextualized way. Moreover, the use of audio media and films can foster students' motivation and interest in learning English, as they provide a break from traditional teaching methods and offer a more interactive and immersive learning environment. Overall, integrating audio media and films in English language instruction is a valuable tool that enhances students' language proficiency and promotes a deeper understanding of the language and its cultural nuances.
Keywords: Film; video; to watch; impression